2016
DOI: 10.1038/bjc.2016.65
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aspirin and nonsteroidal anti-inflammatory drug use after diagnosis on survival of oesophageal cancer patients

Abstract: Background: Aspirin use has been shown to lower incidence and mortality in cancer patients. The aim of this population-based study was to determine the effect of postdiagnosis low-dose aspirin use on survival of patients with oesophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…In patients who had undergone esophagectomy, the risk ratio of the group followed by aspirin treatment versus non-aspirin use group was 0.40 (95% CI, 0.20-0.79) while in the patients who received no esophagectomy the risk ratio was 0.45 (95% CI, 0.31-0.66). Moreover, the survival in patients who had only received post-diagnosis aspirin treatment was better than those had received both pre-diagnosis and post-diagnosis aspirin treatment, which could be explained by the hypothesis that the tumor in pre-diagnosis users has survived in presence of aspirin in plasma, it would also survive the similar dose after post-diagnosis aspirin treatment (26 To get more convincing evidence, a multicenter, doubleblind, phase III randomized controlled trial with four parallel cohorts of breast, colorectal, gastro-esophageal and prostate cancer has been in progress in the United Kingdom (28). In this trial, some participants with standard potentially curative treatment for esophageal cancer, which refers to surgery with standard neo-adjuvant or adjuvant therapy, or only primary chemoradiotherapy, will receive regular different dose of aspirin as an adjuvant therapy.…”
Section: Aspirin As Adjuvant Treatment In Patients With Esophageal Camentioning
confidence: 99%
See 4 more Smart Citations
“…In patients who had undergone esophagectomy, the risk ratio of the group followed by aspirin treatment versus non-aspirin use group was 0.40 (95% CI, 0.20-0.79) while in the patients who received no esophagectomy the risk ratio was 0.45 (95% CI, 0.31-0.66). Moreover, the survival in patients who had only received post-diagnosis aspirin treatment was better than those had received both pre-diagnosis and post-diagnosis aspirin treatment, which could be explained by the hypothesis that the tumor in pre-diagnosis users has survived in presence of aspirin in plasma, it would also survive the similar dose after post-diagnosis aspirin treatment (26 To get more convincing evidence, a multicenter, doubleblind, phase III randomized controlled trial with four parallel cohorts of breast, colorectal, gastro-esophageal and prostate cancer has been in progress in the United Kingdom (28). In this trial, some participants with standard potentially curative treatment for esophageal cancer, which refers to surgery with standard neo-adjuvant or adjuvant therapy, or only primary chemoradiotherapy, will receive regular different dose of aspirin as an adjuvant therapy.…”
Section: Aspirin As Adjuvant Treatment In Patients With Esophageal Camentioning
confidence: 99%
“…Later in 2006, a hospital-based case control study with consistent frequency and duration of drug use of aspirin designed by Jayaprakash et al found a significantly lower risk of esophageal cancer in regular aspirin users compared to non-users (OR =0.54; 95% CI, 0.36-0.86) (25). Studies on antitumor effect of aspirin are focusing on the prevention both of occurrence and recurrence of the disease, and it has been showed post diagnosed aspirin use is more likely to be associated with higher survival rates in patients with esophageal cancer (26). In this regard, it is suggested aspirin could be developed as an adjuvant treatment in patients with cancer (18).…”
Section: Antitumor Effect Of Aspirin In Patients With Esophageal Cancermentioning
confidence: 99%
See 3 more Smart Citations